Homogenized Model of Diffusion in Porous Media with Nonlinear Absorption on the Boundary - Goncharenko, M. V.; Khilkova, L. O. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We consider a boundary-value problem used to describe the process of stationary diffusion in a porous medium with nonlinear absorption on the boundary. We study the asymptotic behavior of the solution when the medium becomes more and more porous and denser located in a bounded domain $Q$. A homogenized equation for the description of the main term of the asymptotic expansion is constructed.